1997
DOI: 10.1007/s002620050368
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral infusion of the monoclonal antibody, mAb 425, against the epidermal-growth-factor receptor in patients with advanced malignant glioma

Abstract: Malignant glioblastoma may over-express the epidermal-growth-factor receptor (EGF-R). Normal brain cells show a low or no expression of EGF-R. A mouse monoclonal antibody (IgG2A) (mAb 425) (EMD55900) (Merck KGaA, Bernstadt, Germany) directed against EGF-R was produced for therapeutic use. Eight patients with primary or recurrent, EGF-R-positive glioblastomas entered the study, which was designed to evaluate the clinical effect of the mAb. In order to achieve a high tumor cell saturation, the mAb was injected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…Part of the effect was probably mediated by the activation of various immune functions with infiltration, in the tumor lesion, of macrophages, granulocytes, CD4 and CD8 T cells. 41 In our study, a unique intracavitary administration of 3 mg of Nimotuzumab labeled with 10 or 15 mCi of 188 Re elicited a dose-dependent cerebral edema and in 3 cases (CR or PR) an unexpected beneficial effect.…”
Section: Discussionmentioning
confidence: 99%
“…Part of the effect was probably mediated by the activation of various immune functions with infiltration, in the tumor lesion, of macrophages, granulocytes, CD4 and CD8 T cells. 41 In our study, a unique intracavitary administration of 3 mg of Nimotuzumab labeled with 10 or 15 mCi of 188 Re elicited a dose-dependent cerebral edema and in 3 cases (CR or PR) an unexpected beneficial effect.…”
Section: Discussionmentioning
confidence: 99%
“…Data have been published indicating that the EGF receptor expression is low or absent in normal human brain tissue. [17][18][19] Other investigators have found EGF receptor expression in various cell types in the normal human brain, although not in glial cells. 20,21 Therefore, before a phase I clinical trial with 425.3-PE can be initiated, its toxicology profile may need to be determined in species other than rat or mice.…”
Section: Immunotoxin Treatment Of Xenografted Human Gliomas In Nude Rmentioning
confidence: 98%
“…16 In another study, the antibody was infused into the margins of the tumor cavity twice weekly using an implanted catheter. 17 Unfortunately, an intense local inflammatory reaction did not permit repeated milligram infusions of the antibody, a reaction that might be expected with the use of intact mouse antibodies in these quantities. Although murine antibodies may elicit a human anti-murine antibody (HAMA) response, such an inflammatory response has not been observed with antibodies conjugated to toxin molecules, possibly because of the relatively small amount of conjugates needed for therapy.…”
Section: Immunotoxin Treatment Of Xenografted Human Gliomas In Nude Rmentioning
confidence: 99%
“…This antibody, along with other EGF receptor-blocking mAbs, inhibits the proliferation of a variety of cultured and xenografted tumour cell lines that are stimulated by the TGF-α/EGF receptor autocrine loop, including cell lines derived from cancers of the vulva (Fan et al, 1993a;1994), breast (Ennis et al, 1989), prostate (Peng et al, 1996;Hofer et al, 1991), ovary (Ye et al, 1999), bladder (Perrotte et al, 1999), kidney (Prewett et al, 1998), lung (Lee et al, 1992), colon (Karnes et al, 1992;Wu et al, 1996), brain (Wersall et al, 1997), and head and neck (Modjtahedi et al, 1993). It has been postulated that these antibodies inhibit tumour cell proliferation by an antibody-mediated interruption of the autocrine activation of EGF receptors in cancer cells (Van de Vijver et al, 1991;Fan et al, 1993b;Baselga et al, 1996).…”
mentioning
confidence: 99%